2022
DOI: 10.1021/acs.macromol.1c01593
|View full text |Cite
|
Sign up to set email alerts
|

RAFT Polymerization of N-Methyl-N-vinylacetamide and Related Double Hydrophilic Block Copolymers

Abstract: Bulk reversible addition−fragmentation chain-transfer polymerization (RAFT) of N-methyl-N-vinylacetamide (NMVA) was explored with four different RAFT agents, which are two xanthates and two dithiocarbamates. Working at 35 °C with an unusually high [V-70] 0 /[RAFT agent] 0 ratio, cyanomethyl O-ethyl carbonodithioate and cyanomethyl diphenylcarbamodithioate allowed the synthesis of poly(N-methyl-N-vinyl acetamide) (PNMVA) with predetermined M n and relatively low dispersities (Đ < 1.5). A good thiocarbonylthio e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…This result was relatively unexpected when considering that these reaction conditions correspond to an initiator to the CTA1 ratio of 0.83, which is way higher than for classical RAFT conditions. A similar phenomenon was encountered in a recent study by our group on the RAFT polymerisation of NMVA, 40 where polymerizations showed an unexpectedly good level of the control of molar masses for an abnormally high [V-70]/ [CTA] ratio of 1.49/1. This result may be ascribed to the low efficiency of V-70 in NVF polymerization.…”
Section: Papersupporting
confidence: 82%
See 4 more Smart Citations
“…This result was relatively unexpected when considering that these reaction conditions correspond to an initiator to the CTA1 ratio of 0.83, which is way higher than for classical RAFT conditions. A similar phenomenon was encountered in a recent study by our group on the RAFT polymerisation of NMVA, 40 where polymerizations showed an unexpectedly good level of the control of molar masses for an abnormally high [V-70]/ [CTA] ratio of 1.49/1. This result may be ascribed to the low efficiency of V-70 in NVF polymerization.…”
Section: Papersupporting
confidence: 82%
“…1), a common phenomenon in RAFT polymerisation of N-vinylamides with xanthate CTAs. 40 These three concentrations correspond to the [V-70] 0 / [CTA1] 0 ratios of 0.83, 0.33 and 0.10, respectively. While the highest conversion (93%) was obtained with [V-70] 0 /[CTA1] 0 = 0.83, the important amount of the initiator relative to CTA1 used could decrease the quality of the control by generating a high proportion of dead chains.…”
Section: Raft Polymerisation Of Nvfmentioning
confidence: 98%
See 3 more Smart Citations